Analisis Peran Dukungan Sosial Dalam Tingkat Kepercayaan Diri Remaja - Salbiah Salbiah; Eklys Cheseda Makaria; Sulistiyana Sulistiyana (Universitas Pakuan, 2026)
Analysis of the Role of Social Support in Adolescent Confidence Levels Abstract. This study is motivated by the importance of adolescence as a critical phase in the development of self-confidence, during which many adolescents still experience doubts about their abilities. The study aims to analyze the role of social support in adolescent self-confidence. A qualitative approach with a phenomenological method was employed to explore the experiences of students at MAN 2 Kota Banjarmasin. The informants consisted of six individuals selected through purposive sampling based on different levels of self-confidence. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model.The results indicate that social support from family, peers, and teachers plays a significant role in shaping self-confidence through attention, acceptance, and motivation. Adolescents who receive adequate social support tend to be more confident, active, and willing to face challenges, while a lack of support is associated with self-doubt and social anxiety. The findings highlight the importance of guidance and counseling services in optimizing social support to enhance adolescents’ self-confidence development. Future research is recommended to involve a larger number of participants and explore additional variables to obtain more comprehensive findings.